THE UTILIZATION STUDY OF PLACE FISH AUCTIONIN VILLAGE PASAR BAWAH SOUTH BENGKULU REGENCY BENGKULU PROVINCE - Jevi '; Jonny Zain; Syaifuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Pasar Bawah village is one of villages in south Bengkulu Regency owning a Place of Fish Auction ( TPI ). Pasar Bawah TPI expected to me community consumption on marine fish locally (Sout Bengkulu Regerency). Pasar Bawah Development was very well done,according to near fishing ground an suported by fisherman’s and armada’s and kualifikasi organizer education which enough nicely. Beside, every day of fish landed always sellout cause the exis of transportation so that the marketing go out area is not annoyed.This research aimed to look at the condition and facility usage which existed in Pasar Bawah TPI and probability for development. The adventage of this research was giving suggestion and consideration to development of TPI facility in the future. The data Analysed consisted of technical analysis . According to the research and result and tehnical count result, the facilities and it’s utilizationKeyword : Utilization,facilities place fishauction, TPI Pasar Bawah.